Household Wealth and Body Mass Index: Towards a Healthy Ageing? - Ignacio Belloc; José Alberto Molina; Jorge Velilla (Global Labor Organization (GLO), 2023)
Studying the impact of exogenous wealth shocks on health-related outcomes can help policymakers in the design and evaluation of social programs that provide income to certain groups. This paper analyzes the impact of unexpected inheritances on Body Mass Index, using data from the Survey of Health, Ageing and Retirement in Europe, including 15 countries from 2004 to 2017. The results show that the receipt of an inheritance is negatively associated with BMI, and being overweight among females. When we account for individual heterogeneity, we find that the receipt of an unexpected inheritance reduces the probability of being overweight by 2.8% among women, and it increases the probability of women engaging in activities that involve moderate physical activity, and increases the amount spent on eating out. These results suggest that large increases in wealth may improve current weight problems and maintain higher life standards among women in later life, so policymakers may include the potential health-related benefits when implementing redistribution programs within those households.
Keywords: G51; I12; J14; O52; 330; Body Mass Index; Unexpected inheritances; Ageing; Europe; SHARE